In-depth analysis of lupeol: delving into the diverse pharmacological profile - Dalimunthe, Aminah; Carensia Gunawan, Mega; Dhiya Utari, Zahirah; Dinata, Muhammad Riza; Halim, Princella; Estherina S. Pakpahan, Nathasya; Sitohang, Alex Insandus; Sukarno, M. Andriansyah; Yuandani,; Harahap, Yahdiana; Setyowati, Erna Prawita; Park, Moon Nyeo; et al. (Frontiers in Pharmacology, 2024)
Lupeol, a naturally occurring lupane-type pentacyclic triterpenoid, is widely distributed in various edible vegetables, fruits, and medicinal plants. Notably, it is found in high concentrations in plants like Tamarindus indica, Allanblackia monticola, and Emblica officinalis, among others. Quantitative studies have highlighted its presence in Elm bark, Olive fruit, Aloe leaf, Ginseng oil, Mango pulp, and Japanese Pear bark. This compound is synthesized from squalene through the mevalonate pathway and can also be synthetically produced in the lab, addressing challenges in natural product synthesis.Over the past four decades, extensive research has demonstrated lupeol's multifaceted pharmacological properties, including anti-inflammatory, antioxidant, anticancer, and antibacterial effects. Despite its significant therapeutic potential, clinical applications of lupeol have been limited by its poor water solubility and bioavailability. Recent advancements have focused on nano-based delivery systems to enhance its bioavailability, and the development of various lupeol derivatives has further amplified its bioactivity. This review provides a comprehensive overview of the latest advancements in understanding the pharmacological benefits of lupeol. It also discusses innovative strategies to improve its bioavailability, thereby enhancing its clinical efficacy. The aim is to consolidate current knowledge and stimulate further research into the therapeutic potential of lupeol and its derivatives.